Economic Perceptions, Cultural Values, and Supporting Infrastructure as Determinants of Muslim-Friendly Tourism Acceptance: The Moderating Role of Community Resistance in North Toraja - Haidir; Ahmad Syarief Iskandar; Ishak (LP2M IAIN Palopo, 2025)
This study aims to examine the influence of economic perception, cultural values, and supporting infrastructure on the acceptance of Muslim-Friendly Tourism, with community resistance serving as a moderating variable in North Toraja Regency. Using a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM), the research analyzes questionnaire data from local respondents. The results show that economic perception (T = 2.105; p = 0.029), cultural values (T = 2.086; p = 0.037), and supporting infrastructure (T = 3.780; p = 0.000) significantly affect tourism acceptance. Community resistance moderates these relationships by weakening the effects of economic perception (T = 2.288; p = 0.004) and cultural values (T = 2.671; p = 0.015), while strengthening the positive influence of supporting infrastructure (T = 2.027; p = 0.005). Overall, the findings highlight that acceptance of Muslim-Friendly Tourism in non-Muslim regions is shaped not only by economic benefits, cultural norms, and facility availability, but also by the ability to manage community resistance so that tourism initiatives remain aligned with local identity and cultural values.